Combustion characteristics of biodiesel saturated with pyrolysis oil for power generation in gas turbines. (December 2016) - Kurji, H.; Valera-Medina, A.; Runyon, J.; Giles, A.; Pugh, D.; Marsh, R.; Cerone, N.; Zimbardi, F.; Valerio, V.
Abstract: There is a perceived need for multi-fuel burner geometries capable of operating with variable composition fuels from diverse sources to achieve fuel flexibility in gas turbines. The objective of the research covered herein is a comparison study between two liquid fuels, a biodiesel (in a pure form) and the biodiesel as a saturated mixture with a pyrolysis by-product; these two fuels were compared against a standard kerosene as a baseline. The research methodology involved two stages: firstly atomization patterns and injection regimes were obtained using a high speed imaging method, secondly a combustion test campaign was undertaken using a swirl burner to quantify the operational behaviour, species production and exhaust gas compositions of the fuels. Emissions, flame stability trends and power outputs were measured at gas turbine relevant equivalence ratios. Excess oxygen and atomization trends in the biodiesel seem to be playing a major role in the production of emissions and flame stability when compared to kerosene. Also, heavy organics seem to be acting as catalytic substances for OH production close to the burner mouth. In terms of stability and combustion, it is proposed that the saturated blend would be a viable candidate for power generation. Highlights: Three fuels were compared to define relative performance of a saturated biodiesel. Atomization patterns and injection regimes were obtained. Injection patterns are less likely to provide effective droplet breakup and atomization for saturated biodiesels. Saturated blends will result in higher NOX concentrations with less oxygen and CO emissions. Chemiluminescence was used to provide evidence of localised OH* production and general flame shape.